Использование технологии блокчейн для децентрализованной системы электронного голосования - Курбатов, А. С. (ХНУРЕ, 2019)
Traditional accounting systems require complete user trust. A centralized approach in building payment systems, property accounting registers, voting platforms has its advantages, but at the same time it forces the end user to blindly believe the final state of the accounting system database. Therefore, it is not surprising that the community was interested in the systems, which made it possible to guarantee the compliance of the accounting system’s database with the conducted transactions, while trusting only the mathematical methods on which they are based. The blockchain technology has become the key to building such systems.